Effects of N-K management strategies on nutrient uptake efficiency, lodging resistance, and yield in machine-transplanted rice - Li, Zhixin; Hu, Mingming; Liu, Tao; Tang, Yuan; Liu, Ruhongji; Peng, Zhengbo; Wang, Cheng; Peng, Zhenglan; Wang, Zhonglin; Chen, Zongkui; Yang, Zhiyuan; Sun, Yongjian; et al. (Frontiers in Plant Science, 2025)
IntroductionImbalanced N–K ratios reduce nutrient uptake efficiency while increasing lodging susceptibility, thereby destabilizing yield potential. Optimizing N–K ratios is therefore crucial for improving nutrient efficiency, lodging resistance, and yield potential.MethodsThis study employed the hybrid indica rice cultivar F-you 498 as experimental material. Two K management strategies (basal:panicle = 10:0 and 5:5, denoted as K1 and K2) and three N application regimes (basal:tiller:panicle = 7:3:0, 5:3:2, and 3:3:4, denoted as N1, N2, and N3) were tested. Both fertilizers were applied at identical total rates of 150 kg ha-¹ for N and K to investigate N–K interactions on rice growth and nutrient utilization.ResultsN–K interactions significantly affected dry matter accumulation, nutrient uptake, lodging resistance, and yield. Split potassium application (K2) increased grain yield by 3.06% compared with basal-only application (K1), by increasing productive panicles, spikelets per panicle, total spikelets, and seed-setting rate. K2 enhanced post-heading dry matter translocation and improved N–K uptake, elevating panicle N and K accumulation by 5.01% and 13.70%, respectively. K2 also significantly improved lodging resistance. Under K2, the N3 treatment further increased yield by enhancing the number of effective panicles, grains per panicle, and total spikelets, with average yield increases of 12.17% and 4.77% compared with N1 and N2, respectively. Post-heading dry matter accumulation, remobilization ratio, and contribution rate in N3 were higher than in N1 and N2, with two-year average increases of 25.54%, 5.37%, and 7.42% compared with N1, and 12.68%, 2.76%, and 2.57% compared with N2. N3 also promoted the translocation of N and K. Compared with N1 and N2, N3 increased whole-plant N translocation and N transferred to the panicle by 38.09% and 27.45%, and by 14.53% and 12.45%, respectively; whole-plant K translocation and K transferred to the panicle increased by 11.46% and 28.26%, and by 13.35% and 18.35%, respectively. Additionally, N3 improved lodging resistance by thickening internodes and stem-sheath walls. The lodging index was significantly negatively correlated with N and K accumulation in stem-sheaths.DiscussionOverall, the K2N3 combination enhances post-heading assimilate allocation and nutrient translocation in machine-transplanted rice, strengthens stem mechanical properties, optimizes panicle traits, and ultimately achieves stable and high yields.